Profile of Physical Fitness Level of Students - High School Students in Trenggalek Regency Based on TKJI (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The era of globalization was currently existing cultural shifts, in terms of communication, transportation and technology which have an impact on the lack of physical activity and sports activities of youth participants.. This study aims to determine the level of physical fitness of X (ten) grade high school students in the district of Trenggalek. Research uses a qualitative approach through a series of tests and measurements based on TKJI. The population of this study were all students of class X (ten) who had just entered the high school level. The study was conducted in 9 schools that had received recommendations and permits from the school with a total sample of 1,264 research students from public and private high schools. The results of research that have been done that the physical fitness level of students in the District of Trenggalek at the high school level of class X, 61% are in the category of Less inversely proportional to the level of fitness of students who are in the Medium category of 13% and good 1% based on TKJI. Whereas for the body mass index results 54% in the Normal level and 12-16% included in the category of Light and light skinny. The conclusion of this study is that there is a need for physical education learning that can maximize physical activity activities and sports activities of students in daily life.